Practical perspective of cricket ball swing - Scobie, J. A.; Shelley, W. P.; Jackson, R. W.; Hughes, S. P.; Lock, G. D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2020)
A cricket ball has an encircling, stitched seam proud from the leather, separating the surface into two distinct hemispheres. When angled, this seam is exploited by the skilful bowler to create an asymmetry in the viscous boundary layer and the ball will swing. In this article, the fluid dynamics of both conventional swing and reverse swing are explained and demonstrated. Using balls worn under match conditions and insight from a professional cricketer, factors affecting swing were tested experimentally in a wind tunnel. The surface condition of the ball was demonstrated to have a substantial effect on the amount of swing: conventional swing was most obvious for a new, polished cricket ball and the swing reduced as the ball accumulated wear as would happen as the match progresses; reverse swing was seen at high bowling speeds with a worn ball. Humidity in isolation was shown to have no significant effect on swing, dispelling a long-standing myth in the cricketing community. A grid was used to simulate atmospheric convective micro-turbulence above a cricket pitch on a hot day without cloud cover; strong evidence suggested that turbulence inhibits the fragile conditions necessary for laminar flow and prevents swing.